Government intervention and the cost of capital to Irish manufacturing-industry - Ruane, Frances P.; John, A. Andrew (Economic & Social Studies, 1984)
This paper derives some general expressions for the debt cost of capital to the Irish manufacturing sector, incorporating the interaction between fiscal and financial policies. A range of estimates of the actual cost (per cent per annum) of fixed assets in manufacturing is presented for the period 1958-1982. The estimates reinforce the findings of earlier studies that government intervention designed to encourage industrial employment has dramatically reduced the relative cost of capital to labour over the past twenty-five years.
Keywords: Manufacturing - Ireland - Costs; Employment - Industry - Ireland